2022
DOI: 10.3390/microorganisms10010121
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pre- and Probiotic Product Combinations on Ex vivo Growth of Avian Pathogenic Escherichia coli and Salmonella Enteritidis

Abstract: Due to the global spread of antibiotic resistance, there is a strong demand to replace antimicrobial growth promotors in livestock. To identify suitable additives that inhibit the growth of avian pathogenic Escherichia coli O1/O18 and Salmonella enterica serotype Enteritidis strains, an ex vivo screening was performed. Inulin and fructooligosaccharides (FOS) were investigated as prebiotics. Enterococcus faecium and Bacillus coagulans served as probiotic strains. Firstly, the pathogen was anaerobically incubate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our study also identified AMR in E. coli isolated from flocks with no previous antimicrobial use history (e.g., tetracyclines and aminoglycosides resistance), stressing the importance of future studies to identify additional risk factors besides AMU (aspects of biosecurity including downtime/rest period, cleaning and disinfection and use of premise disinfectants) that impact the development of AMR. In addition, future studies should evaluate the effectiveness of antimicrobial alternatives (e.g., prebiotics, probiotics) (Brown et al, 2017;Fuhrmann et al, 2022;Reddy et al, 2022) to reduce the emergence of resistance to individual and multiple antimicrobial classes. This study methodology could be used to evaluate the AMU-AMR linkages in other animals as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified AMR in E. coli isolated from flocks with no previous antimicrobial use history (e.g., tetracyclines and aminoglycosides resistance), stressing the importance of future studies to identify additional risk factors besides AMU (aspects of biosecurity including downtime/rest period, cleaning and disinfection and use of premise disinfectants) that impact the development of AMR. In addition, future studies should evaluate the effectiveness of antimicrobial alternatives (e.g., prebiotics, probiotics) (Brown et al, 2017;Fuhrmann et al, 2022;Reddy et al, 2022) to reduce the emergence of resistance to individual and multiple antimicrobial classes. This study methodology could be used to evaluate the AMU-AMR linkages in other animals as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics can inhibit the growth of Escherichia coli in the mucous layer, thus preventing infection in the host (Zou et al, 2020). In addition, the prebiotic fermentation process by probiotic bacteria will cause the intestinal environment to become acidic, thereby inhibiting the growth of Escherichia coli (Orr et al, 2019;Fuhrmann et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The feed composition and analyzed nutrient contents of the diets are shown in Table 6 (complete analysis is shown in Supplementary Table S8 ). The pre-/probiotic combination was selected according to its promising effect on growth inhibition of E. coli O1/O18 in a preliminary ex vivo study [ 65 ]. A commercial granulated probiotic product containing E. faecium DSM 7134 (1 × 10 10 cfu/g additive, Bonvital ® , LACTOSAN GmbH & Co. KG, Kampfenberg, Austria) was used at a dose of 0.1 g/kg diet according to the manufacturer’s recommendations for minimum inclusion level.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 250 mg crop and cecal contents (for 16S rDNA sequencing) or excreta samples (for qPCR), respectively. A commercial extraction kit (QIAamp PowerFecal Pro DNA Kit, Qiagen, Hilden, Germany) was used according to the manufacturer’s protocol, except for an additional lysis step at 65 °C for 10 min, as previously described [ 65 ]. Thereafter, the DNA extracts were frozen at −30 °C until further analysis.…”
Section: Methodsmentioning
confidence: 99%